Empowering EFL Learners in Persuasive Writing: E-Mind-Mapping (E-M-M) Technique vs. Teaching Rhetorical Devices (RDs) - Nasim Nasr-Esfahani; Mohsen Mahmoudi-Dehaki (Research in English Language Pedagogy)
This study examined the potential effects of implementing the E-Mind-Mapping (E-M-M) technique vs. teaching Rhetorical Devices (RDs) on the overlooked yet frequently used persuasive writing skill among Iranian EFL learners. Following a quasi-experimental design, 52 Iranian upper-intermediate EFL learners were conveniently selected and divided into experimental and control groups in which participants in the former were taught the material using MindMeister mind-mapping software, and the ones in the latter experienced learning ethos, pathos, and logos persuasive strategies for 15 ninety-minute sessions. The instruments included the Oxford Quick Placement Test (OQPT) and valid and reliable writing tests in the pre- and post-test phases. The results showed that while the E-M-M technique and teaching RDs enhanced persuasive writing among Iranian EFL learners, the aforementioned effect was considerably more beneficial compared to the influences of the second-mentioned. The outcomes may benefit TEFL, including EFL teachers, learners and teacher trainers, educational technology, and educational psychology.